Hydrophobic metal halide perovskites for visible-light photoredox C-C bond cleavage and dehydrogenation catalysis - Hong, Zonghan (2019)
Two-dimensional lead and tin halide perovskites were prepared by intercalating the long alkyl group 1-hexadecylammonium (HDA) between the inorganic layers. We observed visible-light absorption, narrow-band photoluminescence, and nanosecond photoexcited lifetimes in these perovskites. Due to their hydrophobicity and stability even in humid air, we applied these perovskites in the decarboxylation and dehydrogenation of indoline acids using (HDA)2PbI4 or (HDA)2SnI4 as photoredox catalysts, with quantitative conversions and high yields for the former. We highlight another original application of the metal halide perovskites.